Ø±Ø¯ÙˆØ¯ ï»‹ï» ï»° Ø£ÙˆÙ‡ïºŽÙ… ïº£ï»®Ù„ ïº£ï»– ïº£ïº®ï»³ïº” Ø§ï»Ÿï»¤ïº®Ø£Ø© ï»“ï»² Ø§ï»¹ïº³ï»¼Ù… - Zawawi Zawawi (UIN K.H. Abdurrahman Wahid Pekalongan, 2013)
Abstract : In the western, is still evolving paradigm that discredit Islam to curb the freedom of women and demeaning position. Consequently, there is a movement for